Adolescents' views on oral health care and promotion in Norway: everyday practices, recommendations, and future visions - Høiseth, Marikken; Jasbi, Arefe (Frontiers in Oral Health, 2024)
In this study, we aimed to understand adolescents' perspectives on oral health care and promotion. 9Our research was conducted in the context of Norway's oral health care system, where societal 10 factors like income and education influence health disparities. Despite free public dental care for all 11 residents younger than 19 years, challenges persist in promoting oral health among adolescents, a 12 group whose oral health behavior and literacy remain largely unexplored. A thematic analysis of an 13 anonymized dataset from around 80 adolescents aged 12-20 years, led to the recognition of five 14 central themes: (1) Feeling fresh vs. feeling indifferent: A broad spectrum of attitudes; (2) Bridging 15 gaps, building habits: Collaborative efforts in oral care; (3) "Create good experiences at the dentist so 16 people come back again"; (4) Requested qualities in oral health promoting solutions; (5) Reminder 17 tools for everyday use. Taken together, these themes highlight adolescents' oral health practices and 18 resources, recommendations for dental clinics, and visions for future oral health promotion. The 19 results emphasize the importance of tailored oral health promotion for adolescents. Some reflections 20 on the theme of social inequalities are provided.